Heart rate response and rating of perceived exertion in novice subjects during Indoor Cycling Session - J. M. Muyor; P. A. López (Asociación Española de Ciencias del Deporte, 2010)
Indoor Cycling has become a popular cardio-vascular activity for group exercise classes in the fitness centers. The purposes of this study were to measure the heart rate response and rating of perceived exertion in novice subjects performing a 45-min indoor cycling session. Fifty-nine subjects volunteered ranged from 13 to 48 years (mean ± SD, age: 32.1 ± 10.2 years old) were recruited from the clients of a private fitness club. They participated in a 45-min Spinning cycle indoor session. Heart rate was measured during the session and the overall rating of perceived exertion (overall-RPE) was measured to finish the session. The indoor cycling session was comprised of a warm-up (10 min), followed by a 25 min trial (cardiovascular phase) of flat, run, seated climb and standing climb activities, followed by a cool down (10 min). The mean values of percentage of heart rate reserve (%HRR) and overall-RPE in the session were 62.1% ± 10.5% and 14.2 ± 1.8 point, respectively. The most time of the session was associated to moderate and hard intensities. The intensity during indoor cycling class in novice adults ranged from moderate to hard values. These data suggest that indoor cycling must be considered a high-intensity exercise mode of exercise for novice subjects. Key Words: indoor cycling; RPE; cardiovascular exercise; fitness.